Understaffing and registered nurses' turnover: The moderating role of regular rest breaks. (August 2017) - Wendsche, Johannes; Hacker, Winfried; Wegge, Jürgen
Current demographic and occupational changes call for new interventions to promote staff retention, especially in nursing where understaffing promotes turnover by increasing workload and strain. Based on previous research examining recovery at work, we investigated whether well-designed rest breaks can function as a resource that buffers adverse consequences of understaffing in nursing. We used a cross-sectional, multi-method study design and assessed understaffing of registered nurses, their regularity of rest breaks, and their annual turnover behaviour in 80 German geriatric nursing teams. As expected, understaffing positively predicted turnover only in work conditions with irregular rest breaks. Hence, implementing regularly scheduled rest breaks can be considered as an effective intervention for improving retention of nurses even in a situation of understaffing.